The effect of eight weeks of high-intensity interval training vs. continuous training on serum Irisin levels and expression of skeletal muscle PGC-1α gene in male rats with metabolic syndrome - Zohreh Borhani Kakhki; Sheila Naibifar; Hossein Nakhaei; Elham Ghasemi (فیزیولوژی ورزش و فعالیت بدنی, 2022)
Purpose: An imbalance in the production of PGC-1α and myokines impairs the energy expenditure, increases adipocyte and develops metabolic pathologies, but physical exercise is able to regulate the secretion of myokines through PGC-1α. The aim of this study was to evaluate the effect of eight weeks of high-intensity interval training vs. continuous training on serum Irisin levels and expression of skeletal muscle PGC-1α gene in male rats with metabolic syndromeMethods: 32 Wistar male rats, with six weeks’ age and weight 150-180 gr, randomly divided into two groups including standard diet (n=8) and high fat diet (n=24). They were then placed on a pre-exercise diet for 12 weeks. 24 rats from high fat diet group were divided randomly into two groups including metabolic syndrome control (Ctr+MS), continuous running (CT-MS) and Interval running (IT-MS). Continuous and interval training for eight weeks were performed on 65-75 and 80-100% of the maximum speed on the treadmill for mice, respectively. The ELISA method for measuring serum Irisin levels and real-time PCR method for expression of PGC-1α gene were used. The data were analyzed by one-way analysis of variance (ANOVA), Tukey's post-hoc test and Pearson correlation at P < 0.05 level.Results: After eight weeks of interval and continuous training, PGC-1α expression (P = 0.01 and P= 0.001) and serum levels of Irisin (P = 0.01 and P= 0.001) increased compared to the metabolic syndrome control group, and this increase was more evident in the interval group than the continuous group (P = 0.001). Muscle expression of PGC-1α was also positively correlated with serum Irisin levels in mice (P = 0.001, r = 0.8).Conclusion: It seems that the use of interval exercises can increase the expression of PGC-1α gene and Irisin as much as continuous exercise and possibly improve metabolic disorders in people with metabolic syndrome.